Analysis of colorectal cancer outcomes for the Australian National Bowel Cancer Screening Program. Issue 1 (25th January 2016) - ,; ,
Abstract: The Australian National Bowel Cancer Screening Program (NBCSP) was introduced in Australia in 2006 with the aim of reducing morbidity and mortality from colorectal cancer. This study looked to evaluate the effectiveness of the NBCSP against this aim. The study linked 2006–2008 NBCSP invitees to colorectal cancer incidence and mortality data and categorized NBCSP invitees diagnosed with colorectal cancer into screen‐detected, interval cancer and nonparticipant subgroups. Colorectal cancers in those not invited into the NBCSP were categorized as the never invited group. Proportional hazards and logistic regression were used to compare mortality, summary stage and other characteristics between groups. Of 12 689 people diagnosed with colorectal cancer in 2006–2008, the never invited group (10 080 cases) had a 15% higher risk of colorectal cancer death by 31 December 2011, compared with NBCSP invitees (after correcting for lead‐time bias). Of the colorectal cancers with "summary stage at first presentation" data (27% of total), diagnoses in the never invited group had 38% higher odds of being more advanced than those diagnosed in NBCSP invitees (distant cancer 19% vs 11%). NBCSP invitees had less risk of dying from colorectal cancer, and were more likely to have less‐advanced colorectal cancers when diagnosed, than noninvitees.